Islamic education philosophy in Malay manuscript : a study based on MSS 2906(A) Bāb al-Adab - Mohd Anuar Mamat; Muhammad Mustaqim Mohd Zarif (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2022)
The acceptance of Islam by the people in the Malay Archipelago has led to the development of a new form of education based on this religion. The Malay scholars played important roles not only in the aspects of education and society but also in the political and administrative arenas. Their thought and ideas in various disciplines marked the composition of the traditional Malay intellectual corpus and are mostly recorded today in the form of manuscripts. Nonetheless, aspects relating to the exposition of the Islamic philosophy of education are rarely addressed by them, albeit only in a few works dedicated to the subject of knowledge and learning. Hence, this article aims to identify and analyse important elements of the Islamic philosophy of education as understood by the Malays based on the manuscript of MSS 2906(A) Bāb al-Adab, held by the National Library of Malaysia. Among the issues discussed include the concept of knowledge, educational purpose, and the manners of teacher-student relationship notwithstanding the Codicological analysis of the manuscript concerning its origins, authorship and content. All these are aimed at exposing the roles and contributions of the Malay scholars in shaping the educational philosophy discourse in the region as exemplified by various traditional educational institutions such as pondok, pesantren, dayah, meunasah and so on. The perennial elements of the Islamic philosophy of education are very useful in providing the future direction of the present day Islamic educational institutions in facing future challenges.